TRANSPORT AND MINING MACHINES OPERATORS’ BEHAVIORAL ATTITUDES IN SAFETY CLIMATE CONTEXT - Spasojević-Brkić, Vesna K; Veljkovic, Zorica; Brkic, Aleksandar; Misita, Mirjana; Perisic, Martina; Papic, Neda (Journal of Applied Engineering Science, 2022)
As industrial systems represent a complex socio-technical system, it is necessary to analyse the impact of manager-operator-machine interaction on industrial safety, as categories of contextual factors. However, modern scientific literature indicates insufficient research on this topic. This paper has an aim to empirically analyse behavioural style and transport and mining machines operators’ attitudes in the safety climate context. Participants in this study were 28 crane’s and 65 mining machinery’s (excavators, bucket wheel excavators, bulldozers, loaders, graders, backhoe loaders, trenchers, dump trucks and scrapers) operators working in Serbian industrial companies. In the first step there is conducted descriptive statistics and followed by Kolmogorov’s and U* Mann-Whitney test to examine differences. Obtained results have shown that there were not statistically significant differences both between attitudes of operators on those two kinds of machines, namely, there are no statistically significant differences in terms of absenteeism due to poor working conditions, atmosphere of cooperation and togetherness among operators and the ways in which managers motivate and reward them. Between numbers of injuries at work happened by both machines’ types used there are no statistical differences, too. Also, further factor analysis has shown that examined operators’ and machines’ characteristics divide into two factors – one is focused to anthropometric characteristics presented by height and weight while another is focused on age of operator and machine and operator’s experience. It is recommended, in future research to enlarge sample, repeat statistical testing and analyse wider set of variables on examined matters in aim to discover pattern of anthropometric factors influence on behavioural factors.